'Almost None': Women Sociologists and the Study of Women's Crime in Early 20th-Century China and the U.S. Issue 2 (17th November 2023) - Montgomery, Stephanie M.
Abstract: The question of how and why women committed crimes was a topic of hot debate in 1930s Republican China. Although men sociologists during this period largely framed the origins of both men's and women's crime as a social issue, they nonetheless still seriously considered biological and physiological factors in women's motivation for crime. At the same time, women sociologists who authored the two most comprehensive 1930s studies on women's crime – Zhou Shuzhao and research team Liu Qingyu and Xu Huifang – pushed back on the connections between biology and physiology in relation to crime for both women and men. Instead, they argued unconditionally for the social causes of all crime and particular social challenges for Chinese women. Their methodologies and frameworks were especially influenced by work from the Chicago school of sociology, a department which itself produced a number of prominent women social scientists. This article traces the transnational conversation on women's crime in Republican China through the work of U.S. sociologists who were cited by Zhou, Liu, and Xu; research by Chinese men sociologists, especially prominent sociologist Yan Jingyue; and finally, Zhou, Liu, and Xu's own rebuttals, conclusions, and contributions in developing a theory of Chinese women's crime. By also comparing the work of Chinese and U.S. women social scientists, this article argues that both groups pushed back, with varying strategies, on their men colleagues' inordinate focus on criminalized women's biology and physiology. In this way, both Chinese and U.S. women social scientists spoke into a largely male-dominated conversation and provided novel theories of women's crime as women themselves.